2020
DOI: 10.1186/s12974-019-1689-8
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dysfunction mediated through dynamin-related protein 1 (Drp1) propagates impairment in blood brain barrier in septic encephalopathy

Abstract: Background Out of the myriad of complications associated with septic shock, septic-associated encephalopathy (SAE) carries a significant risk of morbidity and mortality. Blood-brain-barrier (BBB) impairment, which subsequently leads to increased vascular permeability, has been associated with neuronal injury in sepsis. Thus, preventing BBB damage is an attractive therapeutic target. Mitochondrial dysfunction is an important contributor of sepsis-induced multi-organ system failure. More recently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(93 citation statements)
references
References 35 publications
4
89
0
Order By: Relevance
“…The occurrence of SAE is one of the main manifestations of organ dysfunction caused by sepsis, excluding clinical or laboratory evidence of a central nervous system infection, a structural abnormality, or another encephalopathy (such as hepatic encephalopathy or uraemic encephalopathy); SAE refers to a diffuse brain dysfunction resulting from sepsis and is mainly exhibited as delirium, cognitive impairment, decreased learning and memory ability, coma, twitch and so on [3,6]. The mechanism may involve the dysfunction of cerebral microvascular cells, the loss of blood-brain barrier integrity, mitochondria dysfunction, the activation of microglia and astrocytes, and neuronal death [7,8]. Currently, the diagnostic criteria and potential risk factors for SAE remain incompletely understood, with no reliable means of clinically evaluating sepsis-associated neurological dysfunction [9].…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of SAE is one of the main manifestations of organ dysfunction caused by sepsis, excluding clinical or laboratory evidence of a central nervous system infection, a structural abnormality, or another encephalopathy (such as hepatic encephalopathy or uraemic encephalopathy); SAE refers to a diffuse brain dysfunction resulting from sepsis and is mainly exhibited as delirium, cognitive impairment, decreased learning and memory ability, coma, twitch and so on [3,6]. The mechanism may involve the dysfunction of cerebral microvascular cells, the loss of blood-brain barrier integrity, mitochondria dysfunction, the activation of microglia and astrocytes, and neuronal death [7,8]. Currently, the diagnostic criteria and potential risk factors for SAE remain incompletely understood, with no reliable means of clinically evaluating sepsis-associated neurological dysfunction [9].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies currently published that utilize these compounds are in the context of targeting ischemia-reperfusion injury, typically with significant benefits in mitochondrial morphology and function both in vitro and in vivo ( 277 , 282 285 , 290 , 388 ). There have also been studies examining the use of p110 and thus the proposed disruption of the Fis1-Drp1 interaction in models of sepsis related complications such as cardiomyopathy and encephalopathy ( 389 ), as well as neurological diseases including Huntington’s disease, amyotrophic lateral sclerosis, and Parkinson’s disease; of which, these studies found significant improvement in pathogenesis and downstream effects of the diseases ( 91 , 354 , 390 392 ). These improvements are determined by criteria such as inhibition of excess mitochondrial fission, decreased reactive oxygen species production, improved mitochondrial membrane potential, and decreased apoptosis.…”
Section: Fis1 In Therapeutic Advancements and Drug Discoverymentioning
confidence: 99%
“…TJs are constructed by a complex network of proteins, such as occludin, claudin, junctional adhesion molecules (JAMs), and ZO-1, -2, and -3. Among them, claudin-5 and ZO-1 were found to be particularly important in maintaining junction assembly of BBB endothelial cells, and their absence correlates with BBB disruption [ 34 , 35 , 36 ]. In fact, knockdown of claudin-5 results in increased permeability of BBB endothelial cells [ 34 ].…”
Section: Discussionmentioning
confidence: 99%